ANALYSIS OF THE IMPLEMENTATION OF BLENDED LEARNING MODEL AT ITBA DIAN CIPTA CENDIKIA (DCC) - HARTIWI, JUNI (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
This research was done to have an analysis to the implementation of Blended Learning Model in teaching learning process after the era of post-Covid-19 pandemic. The teachers of the college became the focus as the main data source. A qualitative approach with a case study design and used simple analysis was employed to only reveal the phenomena that occurred in teaching learning process in ITBA DCC during the era of post-covid-19 pandemic. The results indicated that the teachers already put on a trial in utilizing the technology to handle the teaching process by employing Blended Learning model. Some existed from both the teachers and the learners, as in process of teaching the material, in understanding the instructions of the teachers, the narrow width of interaction between teachers and learners, between learners and learners, and the troubles in delivering the tasks for example videos due to its large size of file. ABSTRAK Penelitian ini dilakukan untuk menganalisis implementasi Model Pembelajaran Campuran dalam proses belajar mengajar pasca-pandemi Covid-19. Dosen perguruan tinggi menjadi fokus sebagai sumber data utama. Pendekatan kualitatif dengan desain studi kasus dan analisis sederhana digunakan untuk mengungkap fenomena yang terjadi dalam proses belajar mengajar di ITBA DCC selama era pasca-pandemi Covid-19. Hasil penelitian menunjukkan bahwa para guru telah mencoba memanfaatkan teknologi untuk menangani proses pengajaran dengan menggunakan model Pembelajaran Campuran. Beberapa kendala muncul baik dari guru maupun peserta didik, seperti dalam proses penyampaian materi, pemahaman instruksi guru, interaksi yang kurang antara guru dan peserta didik, serta kesulitan dalam penyampaian tugas, misalnya video karena ukuran file yang besar.